N-Acetylcysteine for Cardiac Protection During Coronary Artery Reperfusion: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Khan, Sher Ali; Campbell, Ashley M.; Lu, Yingying; An, Lingling; Alpert, Joseph S.; Chen, Qin M. (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery reperfusion is essential for the management of symptoms in the patients with myocardial ischemia. However, the benefit of reperfusion often comes at an expense of paradoxical injury, which contributes to the adverse events, and sometimes heart failure. Reperfusion is known to increase the production of reactive oxygen species (ROS). We address whether N-acetylcysteine (NAC) reduces the ROS and alleviates reperfusion injury by improving the clinical outcomes. A literature search for the randomized controlled trials (RCTs) was carried out in the five biomedical databases for testing the effects of NAC in patients undergoing coronary artery reperfusion by percutaneous coronary intervention, thrombolysis, or coronary artery bypass graft. Of 787 publications reviewed, 28 RCTs were identified, with a summary of 2,174 patients. A meta-analysis using the random effects model indicated that NAC administration during or prior to the reperfusion procedures resulted in a trend toward a reduction in the level of serum cardiac troponin (cTn) [95% CI, standardized mean difference (SMD) −0.80 (−1.75; 0.15), p = 0.088, n = 262 for control, 277 for NAC group], and in the incidence of postoperative atrial fibrillation [95% CI, relative risk (RR) 0.57 (0.30; 1.06), p = 0.071, n = 484 for control, 490 for NAC group]. The left ventricular ejection fraction or the measures of length of stay in intensive care unit (ICU) or in hospital displayed a positive trend that was not statistically significant. Among the nine trials that measured ROS, seven showed a correlation between the reduction of lipid peroxidation and improved clinical outcomes. These lines of evidence support the potential benefit of NAC as an adjuvant therapy for cardiac protection against reperfusion injury.